Phenalenyl-based mononuclear dysprosium complexes - Lan, Yanhua; Magri, Andrea; Fuhr, Olaf; Ruben, Mario (Beilstein Journal of Nanotechnology, 2016)
The phenalenyl-based dysprosium complexes [Dy(PLN)2(HPLN)Cl(EtOH)] (1), [Dy(PLN)3(HPLN)]·[Dy(PLN)3(EtOH)]·2EtOH (2) and [Dy(PLN)3(H2O)2]·H2O (3), HPLN being 9-hydroxy-1H-phenalen-1-one, have been synthesized. All compounds were fully characterized by means of single crystal X-ray analysis, paramagnetic 1H NMR, MALDI-TOF mass spectrometry, UV–vis spectrophotometry and magnetic measurements. Both static (dc) and dynamic (ac) magnetic properties of these complexes have been investigated, showing slow relaxation of magnetization, indicative of single molecule magnet (SMM) behavior. Attempts to synthesize sublimable phenalenyl-based dysprosium complexes have been made by implementing a synthetic strategy under anhydrous conditions. The sublimed species were characterized and their thermal stability was confirmed. This opens up the possibility to deposit phenalenyl-based lanthanides complexes by sublimation onto surfaces, an important prerequisite for ongoing studies in molecular spintronics.
Keywords: coordination complexes; dysprosium; magnetism; mononuclear; phenalenyl-based